Avaliação das vacinas de DNA contendo os genes Sm29 e TSP-2 e a utilização dos nanobastões de ouro como uma nova formulação vacinal contra a esquistossomose mansônica - Natan Raimundo Gonçalves de Assis (2016)
Schistosomiasis is an important parasitic disease worldwide affecting more than 207 million people in 76 countries around the world and causing about 250.000 deaths per year. Nowadays, the main strategy adopted for the control of schistosomiais is the use of safe chemotherapy, as the use of praziquantel. However, the high rates of reinfection after the treatment restrict it as a strategy and assume the need for other forms of control such as vaccination. Sm29 and tetraspanin-2 are two proteins localized in S. mansoni tegument of adult worms and schistosomula, and are considered as powerful vaccine candidates. In this study, we aim to evaluate DNA vaccines carrying such genes, alone or together in a murine model. By western blot and RT-PCR analysis, we confirmed that studied DNA vaccines were transcribed and translated in BHK-21 cells. We evaluated the worm burden and liver granuloma area reduction, the plasmid pUMVC3/Chimera was the most effective one (31% and 37%, respectively). When the cytokine profile was evaluated, we found production of Th1cytokines such TNF-α and IFN-γ that correlates with protection.. Because of the chemical, physical and immunological characteristics of nanoparticles, nanocarriers got the attention of the researchers. In the field of nanotechnology, the gold nanorods are considered potential vaccine carriers. Herein, we bounded the S. mansoni rSm29 protein to gold nanorods, by a cisteamine functionalization or directly. When worm burden was evaluated, the AuNRs-NH2-rSm29 group of immunized mice showed the best protection levels (29%). Following AuNRs-NH2-rSm29 immunization, we determined a Th1 immunological response in mice with production of IFN-γ and TNF- α. Furthermore, the AuNRs-NH2-rSm29 vaccinate d mice were able to activatedendritic cells in vitro, enhancing MHCII and MHCI expression and production of IL4 1β. In summary, immunization strategy using nanorods has a potential use in vaccine development against infectious diseases as demonstrated here.